Two high-risk susceptibility loci at 6p25.3 and 14q32.13 for Waldenström macroglobulinemia. Issue 1 (December 2018) - McMaster, Mary; Berndt, Sonja; Zhang, Jianqing; Slager, Susan; Li, Shengchao; Vajdic, Claire; Smedby, Karin; Yan, Huihuang; Birmann, Brenda; Brown, Elizabeth; Smith, Alex; Kleinstern, Geffen; et al.
Abstract Waldenström macroglobulinemia (WM)/lymphoplasmacytic lymphoma (LPL) is a rare, chronic B-cell lymphoma with high heritability. We conduct a two-stage genome-wide association study of WM/LPL in 530 unrelated cases and 4362 controls of European ancestry and identify two high-risk loci associated with WM/LPL at 6p25.3 (rs116446171, nearEXOC2 andIRF4 ; OR = 21.14, 95% CI: 14.40–31.03, P  = 1.36 × 10−54 ) and 14q32.13 (rs117410836, nearTCL1 ; OR = 4.90, 95% CI: 3.45–6.96, P  = 8.75 × 10−19 ). Both risk alleles are observed at a low frequency among controls (~2–3%) and occur in excess in affected cases within families. In silico data suggest that rs116446171 may have functional importance, and in functional studies, we demonstrate increased reporter transcription and proliferation in cells transduced with the 6p25.3 risk allele. Although further studies are needed to fully elucidate underlying biological mechanisms, together these loci explain 4% of the familial risk and provide insights into genetic susceptibility to this malignancy. Waldenström macroglobulinemia (WM)/lymphoplasmacytic lymphoma (LPL) is a non-Hodgkin-type B cell lymphoma. Here, the authors identify two risk loci for WM/LPL in a two-stage GWAS involving a family-oversampling approach and provide evidence for a functional role of the non-coding SNP rs116446171.